2019
DOI: 10.26444/aaem/106112
|View full text |Cite
|
Sign up to set email alerts
|

Across-shift changes in upper airways after exposure to bacterial cell wall components

Abstract: Introduction. To assess the across-shift changes of cytokine concentrations in nasal lavage (NAL) samples were collected from workers exposed to bacterial cell wall components present in organic dust in three different occupational environments. Materials and method. The study was conducted in 38 employees including 10 workers from a municipal waste sorting plant (WSP), 20 from a sewage treatment plant (STP) and 8 from an office building (OB), who were established as a reference group, not exposed to organic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In the other areas, mass concentrations were between >0.1 and 1 mg/m 3 . These stationary sampling concentrations are close to some examples reported in previously published studies, which reported ambient concentrations between LOD to 13.33 mg/m 3 in the waste treatment sector of different countries [6,11,20,33,35,36].…”
Section: Airborne Inhalable Gravimetric Dustsupporting
confidence: 90%
See 2 more Smart Citations
“…In the other areas, mass concentrations were between >0.1 and 1 mg/m 3 . These stationary sampling concentrations are close to some examples reported in previously published studies, which reported ambient concentrations between LOD to 13.33 mg/m 3 in the waste treatment sector of different countries [6,11,20,33,35,36].…”
Section: Airborne Inhalable Gravimetric Dustsupporting
confidence: 90%
“…Such levels of personal exposure to inhalable dust for workers in WSPs corroborate previous findings. Indeed, personal exposure to inhalable dust among WPS workers has been investigated for WSPs located in Denmark, Poland, Germany, England and Wales, Korea, the Netherlands, France, and Canada [6,8,10,12,20,[38][39][40]45,[67][68][69]. They revealed personal exposure levels from 0.1 to 62.6 mg/m 3 with a wide range of variation between studies.…”
Section: Size Distribution Of Bioaerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these studies reported on acute and/or chronic symptoms, including bronchitis, cough, and nose irritation or wheezing common among sanitary workers. They had occupation related lung diseases (Ajay et al, 2014); exposed with proinflammatory mediators; interleukin concentrations (Cyprowski, 2019).…”
Section: Occupational Related Respiratory Problemsmentioning
confidence: 99%